Linear groups : the accent on infinite dimensionality - Dixon, Martyn R. (Martyn Russell), 1955-; Kurdachenko, Leonid A., 1949-; Subbotin, Igor Ya., 1950- (Boca Raton : CRC Press, Taylor & Francis Group, 2020)
Linear Groups: The Accent on Infinite Dimensionality explores some of the main results and ideas in the study of infinite-dimensional linear groups. The theory of finite dimensional linear groups is one of the best developed algebraic theories. The array of articles devoted to this topic is enormous, and there are many monographs concerned with matrix groups, ranging from old, classical texts to ones published more recently. However, in the case when the dimension is infinite (and such cases arise quite often), the reality is quite different. The situation with the study of infinite dimensional linear groups is like the situation that has developed in the theory of groups, in the transition from the study of finite groups to the study of infinite groups which appeared about one hundred years ago. It is well known that this transition was extremely efficient and led to the development of a rich and central branch of algebra: Infinite group theory. The hope is that this book can be part of a similar transition in the field of linear groups. Features This is the first book dedicated to infinite-dimensional linear groups This is written for experts and graduate students specializing in algebra and parallel disciplines This book discusses a very new theory and accumulates many important and useful results
"A Chapman & Hall book."
OCLC-licensed vendor bibliographic record.
Keywords: Infinite dimensional Lie algebras; MATHEMATICS / Algebra / General; MATHEMATICS / Geometry / General